2022
DOI: 10.31234/osf.io/xmf3y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring individual differences in the depth of planning

Abstract: While making plans, people have to decide how far out into the future they want to plan: days, months, years, or even longer. Overly short-sighted planning can harm people's well-being in important life domains, such as health, finances, and academics. While self-report scales exist to measure people's planning, people's answers to such questions may be distorted by their desire to make a good impression and conform to norms and expectations. Here, we introduce a method for objectively quantifying people's pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This observation, combined with the high proportion of non-learning models, suggests that there is still room for improvement. Furthermore, planning incurs cognitive costs above and beyond the cost of acquiring information Felso, Jain, & Lieder, 2020;Callaway et al, 2022). Therefore, further work can improve our models by incorporating these additional costs into the reward signals that the models learn from.…”
Section: Discussion and Further Workmentioning
confidence: 99%
“…This observation, combined with the high proportion of non-learning models, suggests that there is still room for improvement. Furthermore, planning incurs cognitive costs above and beyond the cost of acquiring information Felso, Jain, & Lieder, 2020;Callaway et al, 2022). Therefore, further work can improve our models by incorporating these additional costs into the reward signals that the models learn from.…”
Section: Discussion and Further Workmentioning
confidence: 99%
“…Notably, this task also incorporated a predator agent whose actions were incorporated into the tree search simulations, highlighting how this approach can incorporate social information into the decision-making process. Another recent study further exploited this approach to demonstrate that individuals differ in the subjective cost of planning, explaining variability across individuals in planning depth [ 74 ]. Providing further support for the utility of this type of planning strategy in naturalistic environments, one study showed through simulation that tree search planning algorithms are especially advantageous in large, open environments where the agent has an extended visual range, characteristics of many of the terrestrial environments that humans inhabit [ 75 ].…”
Section: Planning In Large and Complex State Spacesmentioning
confidence: 99%
“…Tasks which subjects demanded the most incentives to complete (5)(6)(7) or which subjects tended to avoid in favor of other tasks with equivalent rewards (4,8,9) are considered most effortful. Some costly aspects of these tasks are external, like time on task (10)(11)(12) or the complexity of the cognitive model required by the task (13)(14)(15)(16), but other costs arise from the internal operations necessary to realize external actions.…”
Section: Introductionmentioning
confidence: 99%